Door Lock and Attendance Management System Using Facial Recognition For MZR Global Sdn.Bhd. - Lee, Zhi Hao; Kasim, Shahreen (Applied Information Technology And Computer Science, 2022)
Door Lock and Attendance Management System Using Facial Recognition For MZR Global Sdn.Bhd.